COURSE REVIEW WORKSHOP MARKS CRUCIAL STEP IN ENHANCING TEACHING AND LEARNING ENGLISH COURSES - Rosnani, Ismail; Umi Kalsom, Masrom (Pusat Bahasa Moden (PBM), 2024)
To continuously refine the quality of education imparted, the Division of English Language (DEL) from Centre for Modern Languages (CML) recently conducted its Course Review Workshop (CRW) for Semester II, 2023/2024 session. Held over two days, from the 28th to the 29th of February 2024, the workshop served as a platform for comprehensive evaluation and modification of teaching plans, methodologies, and materials implemented for the current semester.